Rates of hip and knee joint replacement amongst different ethnic groups in England: an analysis of National Joint Registry data. Issue 4 (April 2017) - Smith, M.C.; Ben-Shlomo, Y.; Dieppe, P.; Beswick, A.D.; Adebajo, A.O.; Wilkinson, J.M.; Blom, A.W.; ,
Summary: Objective: Despite a health care system that is free at the point of delivery, ethnic minorities may not always get care equitable to that of White patients in England. We examined whether ethnic differences exist in joint replacement rates and surgical practice in England. Design: 373, 613 hip and 428, 936 knee National Joint Registry (NJR) primary replacement patients had coded ethnicity in Hospital Episode Statistics (HES). Age and gender adjusted observed/expected ratios of hip and knee replacements amongst ethnic groups were compared using indirect standardisation. Associations between ethnic group and type of procedure were explored and effects of demographic, clinical and hospital-related factors examined using multivariable logistic regression. Results: Adjusted standardised observed/expected ratios were substantially lower in Blacks and Asians than Whites for hip replacement (Blacks 0.33 [95% CI, 0.31–0.35], Asians 0.20 [CI, 0.19–0.21]) and knee replacement (Blacks 0.64 [CI, 0.61–0.67], Asians 0.86 % [CI, 0.84–0.88]). Blacks were more likely to receive uncemented hip replacements (Blacks 52%, Whites 37%, Asians 44%; P < 0.001). Black men and women aged <70 years were less likely to receive unicondylar or patellofemoral knee replacements than Whites (men 10% vs 15%, P = 0.001; women 6% vs 14%, P < 0.001). After adjustment for demographic, clinical and hospital-related factors, Blacks were more likely to receive uncemented hip replacement (OR 1.43 [CI, 1.11–1.84]). Conclusions: In England, hip and knee replacement rates and prosthesis type given differ amongst ethnic groups. Whether these reflect differences in clinical need or differential access to treatment requires urgent investigation.